PELATIHAN HIDROPONIK DI DESA POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Report entitled "HYDRAULIC TRAINING IN POMAHAN VILLAGE, KECAMATAN PULUNG, PONOROGO DISTRICT" This is one of the requirements for the Job Training (KKN) in each work program that has been completed in Pomahan village, Pulung District, Ponorogo Regency, East Java. This training is useful for residents in Pomahan village, we also do not forget to run the Community Service Program and aim to share information about the many benefits of the training for residents in Pomahan village. In this report we explain the training in hydroponics and the impact that we can see from this training, which is to add insight and introduce hydroponic plants, ways to cultivate hydroponic plants to be able to enjoy healthier vegetables and beautify the garden in Pomahan Village, Pulung District, Ponorogo Regency.In this report, we explain the training of hydroponics and hydroponic planting procedures and the impact that we can see from this training, namely by starting with introducing plant species to introduce and introducing the process of planting to plants. After training in hydroponic plants, it is hoped that the Kartar Krajan management will know and be able to implement the program immediately, or the program will be entitled "training in hydroponic plants.